A REVIEW PAPER: AN APPROACH FOR MORAL PHILOSOPHY OF DR.B.R. AMBEDKAR - Dr. M. Suresh (Galaxy International Interdisciplinary Research Journal, 2023)
Br. B.R. Ambedkar as a dalit, he understood the logical contradiction on inequality within the Indian social framework and he marked how long we shall continue to deny equality in our social and economic life . He never presents his own caste but represent all those communities who were socially and economically down trodden and described the rights of the depressed sections. We can make free the Dalit community through the various epistemic dimension on liberty, equality, fraternity and educate, agitate, organization and knowledge, right path and compassion, action based on good will, thought based on good will, speech based on good will. The prevailing ethical and political drawbacks sprung from a total misconception of the meaning of human relationship and the problem of the right human relations was the key to his entire thought and action Dr. Ambedkar said and supports the system of fundamental rights of man in the institution of force IndiaMy social philosophy may be said to be enshrined in three words liberty, equality and fraternity. In his philosophy, liberty and equality had a place but he added that unlimited liberty destroyed equality, and absolute equality leaves no room for liberty.